Prevalence and risk factors of intimate partner violence among women in four districts of the central region of Ghana: Baseline findings from a cluster randomised controlled trial - Alangea, D.O.; Addo-Lartey, A.A.; Sikweyiya, Y.; Chirwa, E.D.; Coker-Appiah, D.; Jewkes, R.; Adanu, R.M.K. (PLoS ONE, 2018)
Intimate partner violence (IPV) is a significant global public health problem. Understanding risk factors is crucial for developing prevention programmes. Yet, little evidence exists on population-based prevalence and risk factors for IPV in West Africa. Our objective was to measure both lifetime and past year prevalence of IPV and to determine factors associated with past year physical or sexual IPV experience. This population-based survey involved 2000 randomly selected women aged 18 to 49 years living in 40 localities within four districts of the Central Region of Ghana. Questionnaires were interviewer-administered from February to May 2016. Respondents were currently or ever-partnered, and resident in study area ≥12months preceding the survey. Data collected included: socio-demographics; sexual behavior; mental health and substance use; employment status; 12-month and lifetime experience of violence; household food insecurity; gender norms/attitudes; partner characteristics and childhood trauma. Logistic regression modelling was used to determine factors associated with sexual or physical IPV, adjusting for age and survey design. About 34% of respondents had experienced IPV in the past year, with 21.4% reporting sexual and or physical forms. Past year experience of emotional and economic IPV were 24.6% and 7.4% respectively. Senior high school education or higher was protective of IPV (AOR = 0.51[0.30–0.86]). Depression (AOR = 1.06[1.04–1.08], disability (AOR = 2.30[1.57–3.35]), witnessing abuse of mother (AOR = 2.1.98[1.44–2.72]), experience of childhood sexual abuse (AOR = 1.46[1.07–1.99]), having had multiple sexual partners in past year (AOR = 2.60[1.49–4.53]), control by male partner (AOR = 1.03[1.00–1.06]), male partner alcohol use in past year (AOR = 2.65[2.12–3.31]) and male partner infidelity (AOR = 2.31[1.72–3.09]) were significantly associated with increased odds of past year physical or sexual IPV experience. Male perpetrated IPV remains a significant public health issue in Ghana. Evidence-based interventions targeting women’s mental health, disabilities, exposure to violence in childhood, risky sexual behavior and unequal power in relationships will be critical in reducing IPV in this setting.